A Practical Approach for the Oxidation of Unactivated Csp3H Bonds with o‐Nitro(diacetoxyiodo)benzene as an Efficient Hypervalent Iodine(III)‐Based Oxidizing Agent. Issue 9 (2nd July 2014) - Moteki, Shin A.; Selvakumar, Sermadurai; Zhang, Tiexin; Usui, Asuka; Maruoka, Keiji
Abstract A practical approach for the oxidation of unactivated Csp3H bonds by an ortho‐nitrophenyl‐substituted hypervalent iodine(III) reagent is presented. The nitro group coordinates to the adjacent iodine center through dipolar interaction, which leads to a single substitution of the acetate ligand by tert‐butyl hydroperoxide. As a result, a strong iodanyl radical is formed, which can activate the inert Csp3H bonds in a highly efficient manner. The reagent is stable in the presence of moisture, and can be used for oxidation reactions on semipreparative scale.